MURRAY'S LAW UNDER NON-STATIONARY CONDITIONS (Proceedings of the YSU B: Chemical and Biological Sciences, 2025)
The relationship between radii at nodes of a network of tubular pipelines transporting liquid under non-stationary flow conditions is considered. It is shown that Murray's law is applicable in this scenario as well. However, Murray's law does not hold for the average optimal flow rate, but for the root-mean-square flow rate.
Keywords: vascular network; respiratory network; Young's rule